Circulating Tumor Cells as an Indicator of Treatment Options for Hepatocellular Carcinoma Less Than or Equal to 3 cm in Size: A Multi-Center, Retrospective Study - Zhang, Qiao; Xia, Feng; Gao, Hengyi; Wu, Zhenheng; Cao, Wenjing; Xiang, Qingfeng; Guan, Zhifeng; Su, Yang; Zhang, Weiqiao; Chen, Weiqiang; Mo, Ali; Li, Shuqun (Frontiers in Surgery, 2022)
Background: The status of circulating tumor cells (CTCs) is related to the recurrence of hepatocellular carcinoma (HCC), which is also one of the reasons for the poor prognosis of HCC. The purpose of this study was to explore whether CTCs can help guide the choice of treatment methods for HCC. Methods: This study is a multicenter retrospective study, including 602 patients with HCC. CTCs were detected in the overall cohort before operation. There were 361 patients in the training cohort and 241 patients in the validation cohort. Patients were divided into CTC-negative group (CTCs = 0/5ml) and the CTC-positive group (CTCs ≥ 1/5ml) according to CTCs status. Subgroup analysis was performed according to CTCs status. We compared overall survival, and recurrence outcomes for HCC patients with different CTC statuses after undergoing radiofrequency ablation (RFA) or surgical resection (SR) Results: There was no significant difference in overall survival (OS) and recurrence-free sur-vival (RFS) between the RFA group and SR group for CTC-negative patients in both the training cohort and the validation cohort (P > 0.05). However, among CTC-positive patients, the clinical outcome of patients in the SR group was significantly better than those in the RFA group. CTC-positive patients who underwent RFA had increased early recurrence compared to those who underwent SR. RFA is an independent risk factor for survival and recurrence in CTC-positive HCC patients Conclusions: The CTC status could serve as an indicator to guide the choice between surgical resection or radiofrequency ablation for early hepatocellular carcinoma. Surgical resection is recommended for CTC-positive patients.